Pengaruh Konteks pada Ilustrasi Buku Pendidikan Karakter terhadap Perilaku Disiplin Anak Usia Dini - Lalita Gilang; Riama Maslan Sihombing; Nedina Sari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
This research aims to describe and explain: (1) the difference of influence in disciplinal behavior of the early ages in learning using character education books containing congeniality between context and illustration in the form of story, activity, and activity-comparative; (2) the strongest influence between story, activity, and activity-comparative books containing congeniality between context and illustration to disciplinal behavior of the early age. This research was conducted in TK Kristen Kalam Kudus Surakarta. This research was done with experimental quantitative method. Before the experiment was carried out, early analysis of character education books containing congeniality between context in illustration was done, continued by determining books that fit the criteria in congeniality between context and illustration based on the early analysis and experts’ opinions. The experts including book authors who are proficient in the psychological development of the early age, and teachers of kindergartens. Data retrieval was done using instruments. Instruments and data have been validated theoretically and contextually. The results conclude that there is a significant influence of congeniality between context and illustration to disciplinal behavior of the early age in kindergartens. The strongest influence among the books containing congeniality between context in illustration is activity-comparative books.